Optimization model applied to radiotherapy planning problem with dose intensity and beam choice - Freitas, Juliana Campos de [UNESP]; Florentino, Helenice de Oliveira [UNESP]; Benedito, Antone dos Santos [UNESP]; Cantane, Daniela Renata [UNESP] (Elsevier, 2020)
Optimization applied to radiotherapy planning is a complex scientific issue seeking to deliver both possible highest dose into tumor tissue and lowest one into adjacent tissues. It is composed of one or more of the following main problems: beam choice, dose intensity and blades opening. In this paper, a mixed integer nonlinear optimization model is developed for radiation treatment planned by intensity modulated radiotherapy treatment involving both dose intensity and beam choice optimization problems. Moreover, metaheuristics proposed to solve the beam optimization problem are coupled with exact methods, which in turn solve the dose intensity problem. The proposed model is applied to two real computerized tomography images of prostate cases, where it has been shown to be highly efficient.
Keywords: Dual simplex; Interior point method; Matheuristic algorithms; Primal simplex; Tabu search; Variable neighbourhood search